Are immigrants more vulnerable to the socioeconomic impact of COVID-19? A cross-sectional study in Amadora Municipality, Lisbon metropolitan area - O. Martins, Maria Rosario; Shaaban, Ahmed Nabil; Abecasis, Ana; Muggli, Zelia; Amado, Regina; Vaz, Dora; Dias, Sara S.; Silva, Antonio C.; Fronteira, Ines (Frontiers in Public Health, 2022)
Introduction: Immigrants carry a substantial burden of morbidities and mortalities since the beginning of the COVID-19 pandemic. Pre-existing inequalities among immigrants may threaten their economic well-being during the pandemic. This study analyzed the socioeconomic impact of COVID-19 in immigrants and natives living in Amadora, Metropolitan Region of Lisbon and the extent to which preexisting inequalities had been exacerbated during the pandemic. Materials and Methods: This cross sectional study was conducted in Amadora Municipality, Lisbon Region, through phone interviews and using a structured questionnaire. Data collected in July 2020, included information on a cohort of 420 households, of which 51% were immigrants. To evaluate socioeconomic position and economic well-being changes occurring during the pandemic we estimate crude and adjusted odds ratio (OR) and 95% CI, using Portuguese natives as the reference group. Results: Overall, 287 (70%) of participants responded to the questionnaire, of which 47% are immigrants. Preexisting socio-economic inequalities were exacerbated during the pandemic. Compared with native, immigrants were more likely to experience job loss, temporary lay-off, and income loss during the COVID-19 pandemic. Immigrants were also more likely to face several kinds of financial hardship during the pandemic, such as difficulties in buying food, hygiene products, and paying bills. Conclusion: To the best of our knowledge, this study is the first to capture the direct socioeconomic impact of COVID-19 among immigrants and natives in Portugal. It highlights the bidirectional relation between inequalities deeply rooted among immigrants and COVID-19. Socioeconomic inequalities affect local patterns of COVID-19 burden, as confirmed in previous studies, but COVID-19 also have an impact on the economic well-being of Amadora immigrants during the pandemic. Urgent policies are needed to be implemented to mitigate the economic burden of COVID-19 among immigrants, namely in Amadora, Lisbon Region.